40th Structures, Structural Dynamics, and Materials Conference and Exhibit 1999
DOI: 10.2514/6.1999-1396
|View full text |Cite
|
Sign up to set email alerts
|

Transonic flutter suppression control law design using classical and optimal techniques with wind tunnel results

Abstract: The benchmark active controls technology and wind tunnel test program at NASA Langley Research Center was started with the objective to investigate the nonlinear, unsteady aerodynamics and active flutter suppression of wings in transonic flow. The paper will present the flutter suppression control law design process, numerical nonlinear simulation and wind tunnel test results for the NACA 0012 benchmark active control wing model. The flutter suppression control law design processes using (1) classical, (2) lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…In order to validate the basic structural and the aerodynamic model presented in this paper, openloop simulation results have been compared with the BACT study data obtained by Mukhopadhyay at NASA Langley Research Center [4]. In terms of the flutter dynamic pressure and frequency at Mach number, the numerical model of the NASA study on BACT system gives the following results ⎧ ⎪ ⎨ ⎪ ⎩ P dyn = 6.228 kPa( ∼ =128 psf ) ω = 28.2 rad/s Mach = 0.5 in good agreement with the simulation data of the present model.…”
Section: Open-loop Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to validate the basic structural and the aerodynamic model presented in this paper, openloop simulation results have been compared with the BACT study data obtained by Mukhopadhyay at NASA Langley Research Center [4]. In terms of the flutter dynamic pressure and frequency at Mach number, the numerical model of the NASA study on BACT system gives the following results ⎧ ⎪ ⎨ ⎪ ⎩ P dyn = 6.228 kPa( ∼ =128 psf ) ω = 28.2 rad/s Mach = 0.5 in good agreement with the simulation data of the present model.…”
Section: Open-loop Simulationsmentioning
confidence: 99%
“…During the last decade, extensive work was devoted to active flutter suppression at NASA Langley Research Center. Both the Benchmark Active Control Technology (BACT) project [1][2][3][4][5][6] and the Active Flexible Wing project [7] are considered. The BACT and wind tunnel test programme was started with the objective of investigating non-linear, unsteady aerodynamics and active flutter suppression of wings in transonic flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various flutter control architectures have been developed for AFS, such as the aerodynamic energy concept, 23 classical, 24 linear quadratic Gaussian (LQG), 7,25 , , 26 eigenspace, 27 minimax, 28 predictive, 29 neuro-adaptive, 2,30 and many others. Most of these designs are supported by a few point sensors for feedback.…”
Section: Introductionmentioning
confidence: 99%
“…The time-accurate interaction between structural dynamics, the flight control system, and aerodynamics required for this work (known as aeroservoelasticity), has recently received attention, and previous work by various authors has demonstrated the ability of heave and pitch feedback control acting on conventional control surfaces (e.g. ailerons and spoilers) to increase the flutter margin of both twoand three-dimensional aerofoils in the computational and real domains [12][13][14][15][16][17][18][19][20][21][22][23][24]. However, the gain selection has generally been achieved by standard optimization techniques acting upon a linearized version of the physical system.…”
mentioning
confidence: 99%